Genetic Basis of Left Ventricular Noncompaction. (12th May 2022) - Rojanasopondist, Pakdee; Nesheiwat, Leigh; Piombo, Sebastian; Porter, George A.; Ren, Mindong; Phoon, Colin K.L.
Abstract : Background: Left ventricular noncompaction (LVNC) is the third most common pediatric cardiomyopathy characterized by a thinned myocardium and prominent trabeculations. Next-generation genetic testing has led to a rapid increase in the number of genes reported to be associated with LVNC, but we still have little understanding of its pathogenesis. We sought to grade the strength of the gene-disease relationship for all genes reported to be associated with LVNC and identify molecular pathways that could be implicated. Methods: Following a systematic PubMed review, all genes identified with LVNC were graded using a validated, semi-quantitative system based on all published genetic and experimental evidence created by the Clinical Genome Resource (ClinGen). Genetic pathway analysis identified molecular processes and pathways associated with LVNC. Results: We identified 189 genes associated with LVNC: 11 (6%) were classified as definitive, 21 (11%) were classified as moderate, and 140 (74%) were classified as limited, but 17 (9%) were classified as no evidence. Of the 32 genes classified as definitive or moderate, the most common gene functions were sarcomere function (n=11; 34%), transcriptional/translational regulator (n=6; 19%), mitochondrial function (n=3; 9%), and cytoskeletal protein (n=3; 9%). Furthermore, 18 (56%) genes were implicated in noncardiac syndromic presentations. Lastly, 3 genetic pathways (cardiomyocyte differentiation via BMP receptors, factors promoting cardiogenesis in vertebrates, and Notch signaling) were found to be unique to LVNC and not overlap with pathways identified in dilated cardiomyopathy and hypertrophic cardiomyopathy. Conclusions: LVNC is a genetically heterogeneous cardiomyopathy. Distinct from dilated or hypertrophic cardiomyopathies, LVNC appears to arise from abnormal developmental processes.